Periscopic technique in Norwood operation is associated with better preservation of early ventricular functionCentral MessagePerspective - Puneet Bhatla, MD; TK Susheel Kumar, MD; Luv Makadia, MD; Brandon Winston, MPH; Catherine Bull, PNP-BC; James C. Nielsen, MD; David Williams, MD; Sujata Chakravarti, MD; Richard G. Ohye, MD; Ralph S. Mosca, MD (JTCVS Techniques)
Objective: Although the right ventricle (RV) to pulmonary artery conduit in stage 1 Norwood operation results in improved interstage survival, the long-term effects of the ventriculotomy used in the traditional technique remain a concern. The periscopic technique (PT) of RV to pulmonary artery conduit placement has been described as an alternative technique to minimize RV injury. A retrospective study was performed to compare the effects of traditional technique and PT on ventricular function following Norwood operation. Methods: A retrospective study of all patients who underwent Norwood operation from 2012 to 2019 was performed. Patients with baseline RV dysfunction and significant tricuspid valve regurgitation were excluded. Prestage 2 echocardiograms were reviewed by a blinded experienced imager for quantification of RV function (sinus and infundibular RV fractional area change) as well as for regional conduit site wall dysfunction (normal or abnormal, including hypokinesia, akinesia, or dyskinesia). Wilcoxon rank-sum tests were used to assess differences in RV infundibular and RV sinus ejection fraction and the Fisher exact test was used to assess differences in regional wall dysfunction. Results: Twenty-two patients met inclusion criteria. Eight underwent traditional technique and 14 underwent PT. Median infundibular RV fractional area change was 49% and 37% (P = .02) and sinus RV fractional area change was 50% and 41% for PT and traditional technique (P = .007) respectively. Similarly qualitative regional RV wall function was better preserved in PT (P = .002). Conclusions: The PT for RV to pulmonary artery conduit in Norwood operation results in better preservation of early RV global and regional systolic function. Whether or not this benefit translates to improved clinical outcome still needs to be studied.